PENGARUH PENYALURAN KREDIT TERHADAP PENDAPATAN OPERASIONAL BANK (STUDI KASUS PADA BANK NAGARI CABANG PASAR RAYA PADANG) - Andayani, Suci; Malinda, Yola; Putri, Yosi Eka (Pendidikan Ekonomi, 2014)
BSTRACTIssues that are examined in this study is whether there is any effect of working capital loans, Â investment loans and consumer loans to operating income of Bank Nagari Padang Bazaar branch . This study aims to determine : 1) the effect of working capital loans to operating income of Bank Nagari Padang Bazaar Branch, 2) the effect of investment lending to operating income of Bank Nagari Padang Bazaar Branch, 3) the influence of consumer lending to operating income of Bank Nagari branch Pasar Raya Padang. This type of research is a quantitative study with the location in the Branch Bank Nagari Padang Bazaar and the methodology used is multiple linear regression analysis method. The results showed that : First: Working Capital Lending significantly and negatively related to Operating Income Branch of Bank Nagari Padang Bazaar with a regression coefficient of -1.085 , meaning that if the working capital loans increased 1 billion then the regression coefficient decreased by U.S. $ -1.085 billion with Sig 0.023 < 0.05 . Second: Investment Lending positive and significant impact on Operating Income Branch Bank Nagari Padang Bazaar with a coefficient of 13.775 , meaning that if lending increased by 1 billion investment the regression coefficient increased by Rp 13.775 billion with 0,000 Sig < 0.05. Third: Consumer Lending positive and significant impact on Operating Income Branch Bank Nagari Padang Bazaar with a coefficient of 0183 , meaning that if lending increased by 1 billion investment the regression coefficient increased by USD 0.183 billion to 0.000 Sig < 0.05 .